2014
DOI: 10.3892/etm.2014.1736
|View full text |Cite
|
Sign up to set email alerts
|

IRGM rs13361189 polymorphism may contribute to susceptibility to Crohn’s disease: A meta-analysis

Abstract: The aim of the present meta-analysis was to evaluate the correlation between a common polymorphism, rs13361189 C>T in the immunity-related GTPase M (IRGM) gene, and susceptibility to Crohn’s disease (CD). The PubMed, CISCOM, CINAHL, Web of Science, Google Scholar, EBSCO, Cochrane Library and CBM databases were investigated from database inception through to October 1, 2013 without the application of any language restrictions. The meta-analysis was performed using STATA 12.0 software and the relative risk (RR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…We found that homozygous minor allele status at rs13361189 and rs10065172 were both (as expected given their very high LD) associated with increased risk for CD, but not for UC. Like us, several prior reports have found an association of rs13361189 with CD risk (3,15,27,32,36,38,41,44,47). On the other hand, rs10065172 has been found to associate with CD in some (15,36,41), but not all (27) studies.…”
Section: Discussionsupporting
confidence: 51%
“…We found that homozygous minor allele status at rs13361189 and rs10065172 were both (as expected given their very high LD) associated with increased risk for CD, but not for UC. Like us, several prior reports have found an association of rs13361189 with CD risk (3,15,27,32,36,38,41,44,47). On the other hand, rs10065172 has been found to associate with CD in some (15,36,41), but not all (27) studies.…”
Section: Discussionsupporting
confidence: 51%
“…The most likely reason for the inconsistencies among these studies is that they are single case-control studies with small sample sizes. [ 18 ] The aim of meta-analysis is to combine the same kind of studies to increase the sample size and statistical power, and thereby get a more authentic result.…”
Section: Discussionmentioning
confidence: 99%
“…rs13361189 has also been associated with leprosy 20 and autoimmune thyroid disease 21 , and rs10065172 with tuberculosis 22 and sepsis mortality 23 , collectively suggesting that IRGM regulates a wide spectrum of human disease. A major limitation of the studies performed to date on IRGM and CD risk, however, is that nearly all have been conducted in Europeans 17 , 24 , 25 . Compared to Europeans, Africans have much higher IRGM expression and IRGM rs13361189 risk (C) allele frequency (~ 0.50 vs. 0.10 [useast.ensembl.org]), and much lower LD of rs13361189 to the upstream CNV deletion 16 .…”
Section: Introductionmentioning
confidence: 99%